Structural variability of E. coli thioredoxin captured in the crystal structures of single-point mutants - Noguera, Martín Ezequiel (2017)
Thioredoxin is a ubiquitous small protein that catalyzes redox reactions of protein thiols. Additionally, thioredoxin from E. coli (EcTRX) is a widely-used model for structure-function studies. In a previous paper, we characterized several single-point mutants of the C-terminal helix (CTH) that alter global stability of EcTRX. However, spectroscopic signatures and enzymatic activity for some of these mutants were found essentially unaffected. A comprehensive structural characterization at the atomic level of these near-invariant mutants can provide detailed information about structural variability of EcTRX. We address this point through the determination of the crystal structures of four point-mutants, whose mutations occurs within or near the CTH, namely L94A, E101G, N106A and L107A. These structures are mostly unaffected compared with the wild-type variant. Notably, the E101G mutant presents a large region with two alternative traces for the backbone of the same chain. It represents a significant shift in backbone positions. Enzymatic activity measurements and conformational dynamics studies monitored by NMR and molecular dynamic simulations show that E101G mutation results in a small effect in the structural features of the protein. We hypothesize that these alternative conformations represent samples of the native-state ensemble of EcTRX, specifically the magnitude and location of conformational heterogeneity.